Tinnitus and sound intolerance: evidence and experience of a Brazilian group - Onishi,Ektor Tsuneo (2018)
Abstract Introduction Tinnitus and sound intolerance are frequent and subjective complaints that may have an impact on a patient's quality of life. Objective To present a review of the salient points including concepts, pathophysiology, diagnosis and approach of the patient with tinnitus and sensitivity to sounds. Methods Literature review with bibliographic survey in LILACS, SciELO, Pubmed and MEDLINE database. Articles and book chapters on tinnitus and sound sensitivity were selected. The several topics were discussed by a group of Brazilian professionals and the conclusions were described. Results The prevalence of tinnitus has increased over the years, often associated with hearing loss, metabolic factors and inadequate diet. Medical evaluation should be performed carefully to guide the request of subsidiary exams. Currently available treatments range from medications to the use of sounds with specific characteristics and meditation techniques, with variable results. Conclusion A review on tinnitus and auditory sensitivity was presented, allowing the reader a broad view of the approach to these patients, based on scientific evidence and national experience.